2019
DOI: 10.3390/ijms20246287
|View full text |Cite
|
Sign up to set email alerts
|

The Zebrafish (Danio rerio) Is a Relevant Model for Studying Sex-Specific Effects of 17β-Estradiol in the Adult Heart

Abstract: Cardiovascular diseases are a major cause of morbidity and mortality, and there are significant sex differences therein. However, the underlying mechanisms are poorly understood. The steroid hormone 17β-estradiol (E2) is thought to play a major role in cardiovascular sex differences and to be protective, but this may not hold true for males. We aimed at assessing whether the zebrafish is an appropriate model for the study of E2 effects in the heart. We hypothesized that E2 regulates the cardiac contractility o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For example, the steroid hormone 17βestradiol (E2) and its receptors (ER) are thought to play a major role (107)(108)(109)(110)(111). The E2/ER axis has been shown to have vast effects in the CV system, regulating, for example, contractile function (micro), vascular function, metabolic processes, calcium signaling, gene expression and protein abundance (112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126), which can be sex-dependent (109,(127)(128)(129)(130)(131)(132). Along this line, among various types of hormones with regulatory effects, sex hormones have a key role in the regulation of the distribution of the gut microbiome.…”
Section: Regulation Of the Gut Microbiome By Sex Hormonesmentioning
confidence: 99%
“…For example, the steroid hormone 17βestradiol (E2) and its receptors (ER) are thought to play a major role (107)(108)(109)(110)(111). The E2/ER axis has been shown to have vast effects in the CV system, regulating, for example, contractile function (micro), vascular function, metabolic processes, calcium signaling, gene expression and protein abundance (112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126), which can be sex-dependent (109,(127)(128)(129)(130)(131)(132). Along this line, among various types of hormones with regulatory effects, sex hormones have a key role in the regulation of the distribution of the gut microbiome.…”
Section: Regulation Of the Gut Microbiome By Sex Hormonesmentioning
confidence: 99%
“…A plethora of studies have reported that the E2/ER axis exerts vast effects on the cardiovascular system [ 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ] and that these effects can be sex-dependent [ 14 , 118 , 119 , 120 , 121 , 122 ]. In this context, several pre-clinical data support the notion that E2 facilitates endogenous cardiac repair processes in animal models of ischemia/reperfusion (I/R) and myocardial infarction (MI) [ 101 , 123 ].…”
Section: Role Of E2 In Cardiac Injury and Repairmentioning
confidence: 99%
“…The role of estrogen receptors is indeed crucial in the atherosclerotic process where, in addition to the classical estrogen receptors (i.e., ERα and estrogen receptor-β (ERβ) shown to mediate opposite effects), other receptors may be involved, suggesting that the balance between the different ERs may be responsible for the different responses and effects [23,78]. Moreover, a very recent study on an adult zebrafish model demonstrated that the heart strongly responded to 17β-estradiol in a sex-specific manner, suggesting that zebrafish could be used as a model to identify novel sex-targeted cardiovascular therapies [79]. Finally, a recent study by Tarhouni and co-workers [80] demonstrated an essential role of 17β-estradiol and ERα in flow-mediated remodeling of resistance arteries, suggesting potential synergic impacts of endothelial shear stress and estrogen signaling in terms of vascular adaptation following exercise and training in vivo.…”
Section: Women-specific Cvd Risk Factors and Their Molecular Mechanismmentioning
confidence: 99%